Bibliometric Analysis of Hospital Financial Risk Management Literature in the Era of Economic Uncertainty Based on VOSviewer - Euis Ayu Indah Purnamasari; Lidya Nur Hayya; Ayu Hartati Bakri; Alisiah Rezky; Kosasih Kosasih (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to analyze research trends in the hospital financial risk management literature during the era of economic uncertainty using a bibliometric analysis and a systematic literature review. It focuses on identifying dominant themes, theoretical perspectives, methodological approaches, and emerging trends in hospital financial sustainability, enterprise risk management, adaptive governance, and digital transformation within healthcare organizations. Research Design and Methodology: This study employed a Systematic Literature Review combined with bibliometric analysis, following the PRISMA protocol, including the identification, screening, eligibility, and inclusion stages. Data were collected from Google Scholar, ScienceDirect, Wiley Online Library, and Scopus using keywords related to hospital financial risk management, financial sustainability, healthcare governance, and economic uncertainty. A total of 30 articles published between 2020 and 2025 were analyzed using VOSviewer. Findings and Discussion: The findings show that research has shifted from traditional financial efficiency and cost management toward integrated governance, organizational resilience, and technology-driven sustainability. Four thematic clusters were identified: financial sustainability and operational efficiency; enterprise risk management and resilience; bibliometric mapping; and digital transformation in healthcare governance. Implications: This study emphasizes the importance of sustainability-oriented governance, enterprise risk management, and digital transformation in strengthening hospital financial resilience. It also provides bibliometric mapping and future research directions on adaptive governance and technological innovation in healthcare organizations.